Preparation and characterization of CTAB surfactant modified TiO2 nanoparticles as antibacterial fabric coating material. Issue 1 (1st January 2022) - Bukit, B F; Frida, E; Humaidi, S; Sinuhaji, P
Abstract: TiO2 preparation has been carried out with the addition of cetyl trimethyl ammonium bromide (CTAB) surfactant. The sol-gel method is used in the preparation of TiO2, where TiCl4 is used as a precursor. The resulting TiO2 was characterized using XRD, FTIR, XRF and SEM. XRD results show the crystal size of TiO2 17.75 nm with the rutile phase. The FTIR results show a broad absorption band between 800 and 400 cm −1 by Ti–O vibrations in the crystal lattice. The XRF results showed that the TiO2 content was 80.80%. Morphological results showed an irregular ball-like structure that was less aggregated. The characterization results show that TiO2 can be used as a coating on fabrics with antibacterial properties.